2019
DOI: 10.1038/s41396-019-0358-3
|View full text |Cite
|
Sign up to set email alerts
|

Parental and early life stage environments drive establishment of bacterial and dinoflagellate communities in a common coral

Abstract: The establishment of coral microbial communities in early developmental stages is fundamental to coral fitness, but its drivers are largely unknown, particularly for bacteria. Using an in situ reciprocal transplant experiment, we examined the influence of parental, planulation and early recruit environments on the microbiome of brooded offspring in the coral Pocillopora damicornis. 16S rRNA and ITS2 rDNA gene metabarcoding showed that bacterial and microalgal endosymbiont communities varied according to parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
62
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(72 citation statements)
references
References 21 publications
10
62
0
Order By: Relevance
“…Hydra , for instance, has highly diverse and variable bacterial communities in early life stages but diversity is drastically decreased in the adult stage (Franzenburg et al, ). Several previous studies on corals are also in agreement with our findings (Epstein et al, ; Lema et al, ; Littman, Willis, & Bourne, ). Lema et al () found distinct bacterial communities in the larval stage, early recruit stage (one and 2 weeks old) and recruit/juvenile stages (3, 6, 12 months old) of Acropora millepora .…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Hydra , for instance, has highly diverse and variable bacterial communities in early life stages but diversity is drastically decreased in the adult stage (Franzenburg et al, ). Several previous studies on corals are also in agreement with our findings (Epstein et al, ; Lema et al, ; Littman, Willis, & Bourne, ). Lema et al () found distinct bacterial communities in the larval stage, early recruit stage (one and 2 weeks old) and recruit/juvenile stages (3, 6, 12 months old) of Acropora millepora .…”
Section: Discussionsupporting
confidence: 94%
“…A high abundance of Endozoicomonas spp. has been found in adult corals across geographical regions (Epstein et al, 2019;Morrow, Moss, Chadwick, & Liles, 2012;Pollock et al, 2018). For example, this taxon accounted for >70% of the bacterial communities of Pocillopora damicornis from Australia (van and…”
Section: Winnowing Of Microbial Communitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we did not recover Endozoicomonas‐ related sequences until T 3 , with the highest relative abundance in the final time point (T 8 ). Roseobacter and Burkholderia—Paraburkholderia may also be important for juvenile health by way of nitrogen fixation (Damjanovic, Blackall, Webster, & van Oppen, ; Epstein et al, ; Leite et al, ), although more targeted sequencing is needed to determine if these represent true coral symbionts (e.g., Ainsworth et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The acquisition and development of bacterial and Symbiodiniaceae communities in juvenile varies throughout early stages of coral ontogeny (Abrego, van Oppen, & Willis, , ; Fieth, Gauthier, Bayes, Green, & Degnan, ; Lema, Bourne, & Willis, ; Quigley, Bay, & Willis, ; Quigley, Willis, & Bay, ) likely regulated by both host and environmental factors (Poland & Coffroth, ; Quigley, Bay, et al, ; Quigley, Willis, et al, ; Souza et al, ). In the few species examined to date, the composition of bacterial communities is largely influenced by acquisition from the environmental pool and to a lesser extent by vertical, parental transmission (Apprill, Marlow, Martindale, & Rappé, ; Epstein, Torda, Munday, & van Oppen, ; Leite et al, ; Lema et al, ; Sharp, Distel, & Paul, ; Zhou et al, ). Once acquired, community shifts are common throughout ontogeny across a range of invertebrate groups (Douglas & Werren, ).…”
Section: Introductionmentioning
confidence: 99%